An evaluation of student councils in five agricultural schools of Isabela - Sarangay, Tomas Villa 1924- ([Quezon City s.n.], 1964)
A rating scale for evaluating the status of student councils is developed in this study. The instrument has been used in appraising the effectiveness of student councils in the agricultural high schools of Isabela province.
Thesis (M.Ed.)--University of the Philippines
Keywords: Self government (in education)